SIMULASI SISTEM PROTEKSI MOTOR INDUKSI 3 FASA TERHADAP SUPLAI TEGANGAN TIDAK SEIMBANG DENGAN METODA SIMULINK - Dwi Artika Putra, I Kadek; Arta Wijaya, Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUM, 2021)
The most widespread use of AC electric motors is three-phase induction motors, almost 90% of motor applications in the industry use three-phase induction motors. The operation of 3 phase induction motors generally has voltage imbalance disorders. Voltage imbalance affects several things, including losses and efficiency. This study uses simulation method with the aim to determine the influence of unbalanced voltage on the characteristics of 3 phase induction motor and how to secure a 3-phase induction motor when it gets an unbalanced voltage supply. The result of this simulation obtained the smallest efficiency is 56.8% in the voltage drop condition in one phase and 78.4 in the voltage drop condition in all three phases (R, S and T) with voltage asymmetry of 20% and the biggest loss is 11 406 Watts in the voltage drop condition on one phase with voltage asymmetry of 20%. In the simulation of 3 phase induction motor protection system of unbalanced voltage supply obtained by tripping breaker fastest that is at 0.201 s seconds with drop voltage condition 15% in phase S. 3 phase induction motor safety pattern when getting unbalanced voltage supply is to use an unbalanced voltage safety system that has faster tripping delay time.